The Quality of Knowledge Management in Government: Assessing WhatsApp for Administrative Learning and Professional Dissemination - Praveen Kumar (International Journal of Educational Qualitative Quantitative Research, 2025)
In the era of digital transformation, rapid advancements in Information and Communication Technology (ICT) have transformed the paradigms through which government organizations create and share knowledge to ensure transparency and effective decision-making. This study evaluates the quality of knowledge management (KM) within public administration by assessing the extent, nature, and implications of WhatsApp usage for administrative learning and professional dissemination among 100 government officials in Delhi. Utilizing structured questionnaires and weighted mean score analysis, the findings reveal an exceptional level of digital familiarity (4.83) and a high frequency of usage (4.98), indicating that the platform has become a routine infrastructure for administrative coordination. The application is predominantly utilized for professional learning through organization specific updates (98%), office related resource sharing (93%), and administrative reminders (91%). Although the mean score of 2.83 suggests that digital engagement is strictly task oriented rather than for prolonged personal use, it facilitates a rapid information flow within the governance structure. Despite functional advantages such as quick response (90%) and remote access (97%), significant barriers to quality KM persist, including device storage limitations (80%) and a lack of formal institutional acceptance (71%). Furthermore, unregulated usage contributes to substantial work pressure (90%), stress (79%), and an imbalance between work and life (90%). These findings necessitate the implementation of structured communication guidelines to harmonize operational efficiency with employee well-being. This research contributes to digital governance frameworks by offering empirical insights into bridging the gap between widespread informal digital usage and the requirement for formal, regulated knowledge management practices within public institutions.